Regulation of retinal endothelial cell apoptosis through activation of the IGFBP-3 receptor - Zhang, Qiuhua (2013)
The goal of this study was to investigate whether insulin-like growth factor binding protein-3 receptor (IGFBP-3 receptor) is required for IGFBP-3 to inhibit retinal endothelial cell (REC) apoptosis. REC were grown in normal glucose (5 mM) or high glucose medium (25 mM) for 3 days. Once cells reached confluence, they were transfected with an endothelial- specific IGFBP-3 plasmid DNA (non-IGF binding; IGFBP-3 NB) at 1 μg/ml for 24 h. Cell proteins were extracted and analyzed for IGFBP-3 receptor expression by Western blotting or use in coimmunoprecipitation or co-localization experiments for detection of IGFBP-3 and IGFBP-3 receptor binding. REC were also transfected with or without IGFBP-3 receptor siRNA before IGFBP-3NB plasmid DNA transfection. Cell lysates were processed for a cell death ELISA, a cleaved caspase 3 ELISA, and Western blotting to measure key pro- and anti-apoptotic markers: Bcl-xL, Bax, Cytochrome C and Akt. The IGFBP-3 receptor is present on REC. Overexpression of IGFBP-3 in REC significantly increased protein levels of IGFBP-3 receptor (p < 0.05). Significant increases in cell death were found in cells transfected with IGFBP-3 receptor siRNA versus not treated samples (p < 0.05). Data suggest that IGFBP-3 inhibits retinal endothelial cell death through activation of an IGFBP-3 receptor in a hyperglycemic environment. This is the first demonstration of the involvement of IGFBP-3 receptor in inhibition of REC cell death. Future studies will investigate the mechanism by which IGFBP-3 receptor may inhibit retinal endothelial cell death.